The Douglas Mastriano Scandal: A fraudulent PhD thesis from a Canadian university gets entangled in US politics - Kuhn, Roland (Canadian Perspectives on Academic Integrity, 2023)
This case study looks at how a fraudulent PhD thesis from a Canadian university became entangled in US politics, attracting US and Canadian media attention. In 2013, Douglas Mastriano, a US Army colonel, was granted a History PhD from the University of New Brunswick (UNB) under unusual circumstances. A thesis committee member was removed without his consent, then informed by UNB that the thesis had been approved over his strong objections. UNB declared a 17-year-long embargo on public access to Mastriano’s thesis (it later admitted that its rules limit thesis embargoes to 4 years). In 2014, Mastriano published a book based on his thesis. Respected historians found multiple instances of academic fraud in it, including falsification of archival information. Scholars who requested access to Mastriano’s thesis were rebuffed by UNB. There matters might have rested. However, in November 2022 Douglas Mastriano ran for Governor of Pennsylvania. A Donald Trump supporter and participant in the Jan. 6, 2021 US Capitol invasion, he often cited his PhD from UNB during his campaign. Under media pressure, UNB released his thesis in October 2022. So far, 213 cases of serious academic fraud have been found in it. Before November 2022, UNB promised that “two independent investigators” would investigate Mastriano’s 2013 thesis and the 17-year-embargo on access to it. Subsequently, UNB has walked back that promise. Attendees will learn about the practical and ethical issues faced by a Canadian university when an old case of academic fraud unexpectedly becomes a source of controversy in the media. Disclaimer: This abstract and presentation does not represent the views of Roland Kuhn's employer.